2006
DOI: 10.1677/erc.1.01058
|View full text |Cite
|
Sign up to set email alerts
|

Loss of parafibromin expression in a subset of parathyroid adenomas

Abstract: Inactivation of the hyperparathyroidism-jaw tumour syndrome (HPT-JT) gene, HRPT2, was recently established as a genetic mechanism in the development of parathyroid tumours. Its encoded protein parafibromin has tumour-suppressor properties that play an important role in tumour development in the parathyroids, jaws and kidneys. Inactivating HRPT2 mutations are common in HPT-JT and parathyroid carcinomas, and have been described in a few cases of parathyroid adenomas with cystic features. In this study, 46 cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
68
1
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(79 citation statements)
references
References 27 publications
(37 reference statements)
8
68
1
2
Order By: Relevance
“…The following positive controls were used: HeLa cells transfected with plasmid DNA containing full-length HRPT2 cDNA and two parathyroid carcinomas (T4 and T23) for western blot and immunohistochemistry (Juhlin et al 2006), four paraffin-embedded adenomas on the same slide for immunohistochemistry including one with a rim of normal parathyroid (control adenoma 1) and 21 sporadic adenomas (the majority with a normal rim) as normal reference for immunohistochemistry. For sub-cellular fractionation and western blot analysis, frozen samples of two cystic adenomas with or without HRPT2 gene mutation and parafibromin inactivation (corresponding to T20 and T23 in Juhlin et al 2006), one secondary HPT gland, and a regular adenoma (control adenoma 2) were used.…”
Section: Control Samplesmentioning
confidence: 99%
See 3 more Smart Citations
“…The following positive controls were used: HeLa cells transfected with plasmid DNA containing full-length HRPT2 cDNA and two parathyroid carcinomas (T4 and T23) for western blot and immunohistochemistry (Juhlin et al 2006), four paraffin-embedded adenomas on the same slide for immunohistochemistry including one with a rim of normal parathyroid (control adenoma 1) and 21 sporadic adenomas (the majority with a normal rim) as normal reference for immunohistochemistry. For sub-cellular fractionation and western blot analysis, frozen samples of two cystic adenomas with or without HRPT2 gene mutation and parafibromin inactivation (corresponding to T20 and T23 in Juhlin et al 2006), one secondary HPT gland, and a regular adenoma (control adenoma 2) were used.…”
Section: Control Samplesmentioning
confidence: 99%
“…For sub-cellular fractionation and western blot analysis, frozen samples of two cystic adenomas with or without HRPT2 gene mutation and parafibromin inactivation (corresponding to T20 and T23 in Juhlin et al 2006), one secondary HPT gland, and a regular adenoma (control adenoma 2) were used. All samples were obtained with informed consent and local ethical approval.…”
Section: Control Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…Tan et al (21) demonstrated loss of parafi bromin nuclear immunoreactivity in 96% of parathyroid carcinomas and in eight of nine adenomas associated to HPT-JT syndrome. Furthermore, normal expression of parafi bromin has been demonstrated in the majority of the sporadic parathyroid adenomas so far studied (20)(21)(22).…”
Section: Introductionmentioning
confidence: 97%